The Role of Parental Attachment Style in Conflict Resolution, Management and Outcome of Attention Deficit Hyperactivity Disorder (ADHD) in Children - Fatahyah, Yahya; Sochos, Antigonos (University of Bedfordshire, 2010)
The aim of this doctoral study is to explore the consequence of caring for a child suffering from Attention Deficit Hyperactivity Disorder for the quality of the parental couple relationship. The study is conducted within the framework of attachment theory and is exploring whether and how caring for a child with ADHD may impact negatively or positively on the bond between the parents and how parents with different attachment styles may respond differently to the challenge. A mixed methods design is used. Participants are being recruited through charity organisations supporting families with ADHD. Parents complete a set of self-report questionnaires measuring relationship adjustment, couple conflict, and adult attachment style and are also being interviewed on these issues based on a semi-structured interview schedule. Quantitative data will be analysed using a range of statistical methods while qualitative data will be subjected to thematic analysis. The findings of this study may lead to the identification of helpful and unhelpful interpersonal strategies used by ADHD parents and inform interventions designed to support families dealing with child ADHD.